SEROPREVALENCE OF AVIAN INFLUENZA VIRUS H5N1 IN MUSCOVY DUCKS IN PT. EPIKUR FARM-TABANAN, BALI - Oagay, Melkias Oagay Melkias; Suartha, I Nyoman; Mahardika, I Gusti Ngurah Kade (Buletin Veteriner Udayana, 2022)
Seroepideminological study of avian influenza virus of H5N1 (AIV-H5N1) in a muscovy duck flock has never been resported. This study was conducted to know the seroprevalence of AIV-H5N1 in a muscovy duck flock in PT EPIKUR Tabanan. Fourty-eght muscovy duck sera were colelcted, in which 23 were under 3 months old and 25 were more than one year old. Antibody to AIV-H5N1 was detected using haemaglutination inhibition (HI) test in deluted and undeluted sera. The delution was made by adding 4 time volume of PBS to 1 time volume of sera. The result shows that the seroprevalence  of AIV-H5N1 in murcovy duck at PT. EPIKUR was 0% in young as well as old ducks.